Experimentation and Research in the Physics Course for the Preparation of Primary School Teachers in Naples - Alessandro Amabile; Annarita Annunziata; Giancarlo Artiano; Emilio Balzano (MDPI AG, 2022)
Physics preparation for primary school teachers has received attention only in recent decades. Research on science education provides useful guidelines, often disregarded. Several interrelated research questions must be addressed by field research, namely, (a) which physics subjects to teach in primary school and its relationships with other sciences, technology, and mathematics; (b) how to prepare teachers to grasp the complexity of their tasks; and (c) how to bridge pre-service and in-service training. In this study, we describe innovative aspects of a course, based on the research and action research of our research group, that aims to overcome the limitations of a purely academic approach. Future teachers are dynamically involved in activities in informal and formal contexts and in the training of in-service teachers' activities. The idea of cognitive resonance and a phenomenological approach to the modeling process are the basis of the activities that integrate key concepts of physics with transversal ones to develop skills in physics, mathematics, technology, and language. Field research carried out with qualitative methods shows that the course, despite being demanding, is well received by students. Dozens of students are then involved in the activities of the group when they start a teaching career at school.